Activity of sodium trimetaphosphate, associated or not with fluoride, on dual-species biofilms - Cavazana, Thamires Priscila [UNESP]; Hosida, Thayse Yumi [UNESP]; Pessan, Juliano Pelim [UNESP]; Sampaio, Caio [UNESP]; Monteiro, Douglas Roberto; Delbem, Alberto Carlos Botazzo [UNESP] (Taylor & Francis, 2019)
This study aimed to evaluate the effect of sodium trimetaphosphate (TMP), either with fluoride (F) or without fluoride, on dual-species biofilms of Streptococcus mutans and Candida albicans. The 72 h biofilms were treated with 0.25%, 0.5%, or 1% TMP solutions, combined or not with 500 ppm F, and analysed by quantification of viable plate counts, metabolic activity, biomass, and extracellular matrix components. Biofilm structure was evaluated by scanning electron microscopy (SEM). TMP significantly reduced the number of S. mutans cells and biomass only when associated to F. Furthermore, fluoride-free TMP promoted significant reductions in biofilm metabolism, while all the tested solutions decreased the contents of the biofilm matrix compared to untreated groups. Regarding biofilm structure, TMP associated with F led to the formation of a less compact biofilm. It was concluded that TMP alone had a reducing effect, mainly on the metabolism and the extracellular matrix components of the biofilms.
Keywords: Biofilms; Candida albicans; fluorides; phosphate; Streptococcus mutans